A scoping review of electroencephalographic (EEG) markers for tracking neurophysiological changes and predicting outcomes in substance use disorder treatment - Bel-Bahar, Tarik S.; Khan, Anam A.; Shaik, Riaz B.; Parvaz, Muhammad A. (Frontiers in Human Neuroscience, 2022)
Substance use disorders (SUDs) constitute a growing global health crisis, yet many limitations and challenges exist in SUD treatment research, including the lack of objective brain-based markers for tracking treatment outcomes. Electroencephalography (EEG) is a neurophysiological technique for measuring brain activity, and although much is known about EEG activity in acute and chronic substance use, knowledge regarding EEG in relation to abstinence and treatment outcomes is sparse. We performed a scoping review of longitudinal and pre-post treatment EEG studies exploring putative changes in brain function associated with abstinence and/or treatment in individuals with SUD. Following PRISMA guidelines, we identified studies published between January 2000 and March 2022 from online databases. Search keywords included EEG, addictive substances (e.g., alcohol, cocaine, methamphetamine), and treatment related terms (e.g., abstinence, relapse). Selected studies used EEG at least at one time point as a predictor of abstinence or other treatment-related outcomes; or examined pre- versus post-SUD intervention (brain stimulation, pharmacological, behavioral) EEG effects. Studies were also rated on risk of bias and quality using validated instruments. Forty-four studies met inclusion criteria. More consistent findings included lower oddball P3 and higher beta at baseline predicting negative outcomes, and abstinence-mediated longitudinal decrease in cue-elicited P3 and resting beta power. Other findings included abstinence or treatment related changes in LPP and N2, as well as in delta and theta power. Existing studies were heterogeneous and limited in terms of specific substances of interest, brief times to follow-ups, and inconsistent or sparse results. Encouragingly, in this limited but maturing literature, many studies demonstrated partial associations of EEG with abstinence, treatment outcomes, or pre-post treatment-effects. Studies were generally of good quality in terms of risk of bias. More EEG studies are warranted to better understand abstinence- or treatment-mediated neural changes, or to predict SUD treatment outcomes. Future research can benefit from prospective large-sample cohorts and use of standardized methods such as task batteries. EEG markers elucidating the temporal dynamics of changes in brain function related to abstinence and/or treatment may enable evidence-based planning for more effective and targeted treatments, potentially pre-empting relapse or minimizing negative lifespan effects of SUD.